HIV DNA levels and decay in a cohort of 111 long-term virally suppressed patients. (24th September 2018) - Golob, Jonathan L.; Stern, Joshua; Holte, Sarah; Kitahata, Mari M.; Crane, Heidi M.; Coombs, Robert W.; Goecker, Erin; Woolfrey, Ann E.; Harrington, Robert D.
Abstract : Background and method: We examined specimens from 111 HIV-infected participants virally suppressed on ART for a minimum of 5 years who had donated serial peripheral blood mononuclear cell (PBMC) specimens to the University of Washington/Fred Hutch Center for AIDS Research (CFAR) Specimen Repository. We determined the HIV proviral copy number per million PBMCs, corrected for CD4 + cell count, in 477 specimens collected after a minimum of 5 years of follow-up and up to 15.5 years of clinical viral suppression. Generalized estimating equation regression was used to examine the association between the reservoir size and time, age at study entry, antiretroviral regimen, and risk factors for HIV acquisition. Results and conclusion: We found that the inter-participant baseline HIV DNA level varied widely between 0.01 and 4.8 pol -copies per microgram genomic DNA and per CD4 + cell number/micoliter; the HIV DNA level declined with time (half-life was estimated at 12 years, 95% confidence interval of 6.2–240 years); the HIV DNA level was lower for those who achieved viral suppression at a younger age; and the HIV DNA level was not affected by the specific antiretroviral regimen used to achieve and maintain suppression. Abstract : Supplemental Digital Content is available in the text